(untitled) (Research, Society and Development, 2024)
The skull of dogs is a complex and diverse bony structure that varies widely among breeds, playing essential roles in protecting the brain, supporting facial structures, and facilitating chewing and breathing. However, cranial malformations in dogs are conditions that, in addition to affecting shape, compromise the function of the skull, resulting in various health problems and potentially being incompatible with life. Based on this, this paper aims to describe the anatomy of the canine skull and compare it with the anatomical changes found in some cranial malformations, as well as their clinical implications, through a narrative literature review. Among the important cranial malformations in dogs, brachycephaly, cleft palate, and acrania stand out due to their frequency and/or severity. Brachycephaly is characterized by a shortened and flattened skull, which can lead to respiratory difficulties and other health issues. Cleft palate is characterized by the presence of an opening or fissure in the palate (roof of the mouth), which can affect both the hard and soft palate, resulting in difficulties eating, drinking, and breathing, as well as increasing the risk of infections. Acrania, on the other hand, is a rare but very severe condition in dogs, characterized by the partial or total absence of the cranial bones, resulting in exposure and vulnerability of the brain tissue. Thus, knowledge of normal cranial anatomy is important to understand the magnitude and severity of the clinical implications of each malformation.